Fast or Slow: How Temporal Work Design Shapes Experienced Passage of Time and Job Performance - Zhao, Helen H; Deng, Hong; Chen, Rocky P; Parker, Sharon; Zhang, Wei (Academy of Management, 2021)
Experienced passage of time, the extent to which employees perceive the passage of work time as being fast or slow, is a fundamental aspect of work experience. We identify two novel temporal work design characteristics that can speed up employees’ experienced passage of time: temporal predictability and task segmentation. Jobs with high temporal predictability do not make employees go through uncertain wait times before embarking on their next task. High task segmentation occurs when a large chunk of work time is segmented by categorically different temporal markers. We tested a model in which temporal predictability and task segmentation affect experienced passage of time, which in turn influences job performance, with five studies: two experiments that established the internal validity of temporal predictability and task segmentation (Studies 1a and 1b), a naturalistic field study in a factory that investigated the natural consequences of distinct temporal work design (Study 2), an organizational field study that constructively replicated the model using a sample of knowledge workers and their supervisors (Study 3), and an online survey in which we connected our model with the broader work design literature (Study 4). Altogether, the studies support a new temporal approach to work design.